Effect of Ethanolic Extract of Ketip Banana (Musa paradisiaca Forma Typiaca) Peel on Sperm Morhology in Mice (Mus musculus) Exposed to Cigarette Smoke - Ilmi, Muhamad Yazid Mizanul; Bahri, Syamsul; Lestari, Tri Ayu (Jurnal Biologi Tropis, 2025)
Cigarette smoke exposure is known to induce oxidative stress that lead to morphological damage in spermatozoa. This study aimed to evaluate the effect of ethanol extract of Ketip banana (Musa paradisiaca Forma typiaca) peel on the recovery of sperm morphological damage in adult male mice (Mus musculus) previously exposed to cigarette smoke. The experiment was arranged in in factorial design with two factors. The first factor was the duration of cigarette smoke exposure (0, 5, 15 and 30 minutes), while the second factor was the concentration of ethanolic banana peel extract (0, 250, and 750 ppm). Adult male mice were exposed to cigarette smoke for a defined duration and subsequently treated with ethanol extract of banana peel at different concentration. Sperm morphology was assesed microcopically by using standard procedures. The statistical analysis results showed that administration of ethanol extract of banana peel (F-value = 16.949 > F-critical = 3.40) significantly reduced the percentage of abnormal sperm morphology that induced by cigarette smoke exposure ((F-value = 26.324 > F-critical = 3.01). This finding suggest that ethanol extract of Ketip banan peel has the potential  to restore sperm morphological damage induced by cigarette smoke. Thus, the ethanol extract of Ketip banana peel may serve as a natural antioxidant in mitigating cigarette smoke-induced sperm damage. However, further studies are required to elucidate the underlying mechanism.